The Significance of Strategic Competence in The Training of Students of Future Teachers of PreDuction Military Education (Eurasian Journal of Learning and Academic Teaching, 2023)
The article talks about the importance of strategic competence in teaching students of future teachers of pre-conscription military training. Strategic competence as one of the significant characteristics of students of future teachers of pre-conscription initial training for successful intercultural communicative activity